Efficacy of renal denervation as an adjunct to pulmonary vein isolation for atrial fibrillation treatment: a systematic review and meta-analysis - Thavabalan, K; Sheikh, M; Phuah, Y; Rajput, SK; Fatima, N; Sutaria, A; Bray, JJH; Ahmad, M; Glatzel, H; Ahmad, R; Snell, L; Kumar, NS; et al. (Oxford University Press, 2024)
Aims: Catheter ablation, consisting of pulmonary vein isolation (PVI), is the most effective treatment modality for the management of symptomatic patients with atrial fibrillation (AF). Unfortunately, this procedure has a considerable relapse rate, ranging from 15 to 50% depending on AF type and other patient factors. Hypertension (HTN) is associated with a higher risk of developing AF and can also be managed with a catheter-based procedure—renal denervation (RDN). This meta-analysis aimed to compare the effect of PVI with and without RDN in hypertensive patients with AF. Methods and results: OVID MEDLINE and Embase were searched on 1 February 2023 and trials that reported the effects of RDN on AF recurrence in hypertensive patients were included. A total of 637 patients across 8 randomised controlled trials were included. The results from the pooled analysis showed that when compared with PVI alone, RDN added to PVI: (1) Lowered AF recurrence [RR 0.67 (0.53, 0.85), P = 0.001, I2 = 23%, NNT = 5.9 patients]; (2) Reduced both systolic blood pressure and diastolic blood pressure, with medium effect size, as reflected by standardised mean differences of 0.5 (P = 0.02, I2 = 80%) and 0.43 (P = 0.006, I2 = 60%), respectively; and (3) was not associated with a decrease in estimated glomerular filtration rate (+7.19 mL/min/1.73 m2, P = 0.15, I2 = 89%). Conclusion: Adding RDN to PVI in patients with AF and resistant HTN was associated with a reduction of blood pressure levels and AF recurrence. Consideration to RDN should be given as an adjunctive treatment for patients with AF and resistant HTN.